Sharp Instrument : A Stab at Identifying the Causes of Economic Growth - Cherif, Reda.; Hasanov, Fuad.; Wang, Lichen (Washington, D.C. : International Monetary Fund, 2018)
We shed new light on the determinants of growth by tackling the blunt and weak instrument problems in the empirical growth literature. As an instrument for each endogenous variable, we propose average values of the same variable in neighboring countries. This method has the advantage of producing variable-specific and time-varying-namely, 'sharp'-and strong instruments. We find that export sophistication is the only robust determinant of growth among standard growth determinants such as human capital, trade, financial development, and institutions. Our results suggest that other growth determinants may be important to the extent they help improve export sophistication.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet